PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR MELALUI MODEL STUDENT FACILITATOR AND EXPLAINING BERBANTUAN MEDIA ROTAR - Munia Ningsih; Sumarwiyah Sumarwiyah; Deka Setiawan (PGSD Universitas Muria Kudus, 2020)
The reseach aims to describe the improvement of the Students outcomes at the fourth grade of SDN 1 Payaman trough the Student Facilitator and Explaining science learning models and rotar media in the seven themes indahnya keragaman di negeriku. The research design is a classroom action research that is conducted in two cycles by the number of subjects 29 students. The data collection of this study utilized the interview, observation, test, and documentation. The data analysis is qualitative and quatitative data. The result of the research showed that Students Facilitator and Explaining this science learning model and rotar media improve the students knowledge. In the cycle one the knowledge domains of IPS in classical terms the percentage got 62.06% and the mean was 72.24, while in the domain of indonesia the percentage got 65.51% and the mean was 74.82. in the cycle two for the domain of IPS was gained with a percentage of 89,65% with the mean 83.62. while on the domain of Indonesia got a percentage of 93.10% with the mean 86.03.